2022
DOI: 10.1002/ccd.30446
|View full text |Cite
|
Sign up to set email alerts
|

Hybrid coronary revascularization (HCR) versus coronary artery bypass grafting (CABG) in multivessel coronary artery disease (MVCAD): A meta‐analysis of 14 studies comprising 4226 patients

Abstract: Objectives To compare the outcomes of hybrid coronary revascularization (HCR) with traditional coronary artery bypass grafting (CABG) in multivessel coronary artery disease (MVCAD). Background HCR has emerged as an alternative to CABG in patients with MVCAD. Through minimally invasive surgical techniques, HCR carries the potential for faster recovery postoperatively, fewer complications, and lower utilization of resources. Methods Systematic search of electronic databases was conducted up to December 2021 and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 62 publications
0
2
0
Order By: Relevance
“…An ongoing multicenter randomized trial will confirm the quality of life and recovery between MIDCAB and standard sternotomy CABG the MIST Trial [25]. This study will eventually corroborate the very good outcomes of Mid-CAB in the long term (more than 20 years) when performed in a carefully selected patient population [26][27][28]. Robotic iterations of this operation are already performed in leading centers worldwide, aiming to establish the maximal level of a true minimally invasive approach and providing good long-term outcomes in patients who are not candidates for conventional CABG [29].…”
mentioning
confidence: 75%
“…An ongoing multicenter randomized trial will confirm the quality of life and recovery between MIDCAB and standard sternotomy CABG the MIST Trial [25]. This study will eventually corroborate the very good outcomes of Mid-CAB in the long term (more than 20 years) when performed in a carefully selected patient population [26][27][28]. Robotic iterations of this operation are already performed in leading centers worldwide, aiming to establish the maximal level of a true minimally invasive approach and providing good long-term outcomes in patients who are not candidates for conventional CABG [29].…”
mentioning
confidence: 75%
“…Guan et al in 2019 [ 29 ] published a meta-analysis comparing other modalities of minimal-access CABG with HCR, which summarised eight observational studies and concluded that HCR was non-inferior to other modalities of minimal-access CABG, in terms of in-hospital mortality, rates of MACCE, shock, perioperative MI, long-term survival, cost, and surgical complications. On the other hand, Nagraj et al in 2022 concluded in their meta-analysis of twelve observational studies and two RCTs comparing HCR to conventional CABG via a median sternotomy in multivessel coronary artery disease that although feasible, HCR did not have any clear benefits over conventional surgery [ 68 ].…”
Section: Techniques Of Minimal-access Coronary Artery Revascularisationmentioning
confidence: 99%